2007
DOI: 10.17221/1871-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of blue honeysuckle

Abstract: We have developed a rapid shoot multiplication procedure for <I>in vitro</I> propagation of blue honeysuckle (<I>Lonicera kamtschatica</I> [Sevast.] Pojark). Shoot tips of two genotypes 20/1 and Altaj were successfully established <I>in vitro</I> and micropropagated on the Murashige and Skoog (MS) based media containing different concentrations of 6-benzylaminopurine (BAP). Multiplication rates varied depending on the genotype and concentration of BAP. The highest multiplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 6 publications
2
21
0
1
Order By: Relevance
“…It was probably due to the toxicity of used concentration of mercuric chloride to plant tissues of two selected sweet cherry cultivars. It was previously reported that mercuric chloride is a good disinfectant, but could be toxic to plant tissues of susceptible species and genotypes (Muna et al 1999;Sedlák, Paprštein 2007).…”
Section: Resultsmentioning
confidence: 99%
“…It was probably due to the toxicity of used concentration of mercuric chloride to plant tissues of two selected sweet cherry cultivars. It was previously reported that mercuric chloride is a good disinfectant, but could be toxic to plant tissues of susceptible species and genotypes (Muna et al 1999;Sedlák, Paprštein 2007).…”
Section: Resultsmentioning
confidence: 99%
“…For disinfection the initial explants, chemical solutions such as mercuric chloride (Sedlák and Paprstein 2007), mercuric sulfate (Krupa-Małkiewicz and Ochmian 2014), sodium hypochloride (Karhu 1997;Osburn et al 2009), and calcium hypochloride (Dziedzic 2008) are used. In our study, two disinfectants, mercuric sulfate and sodium hypochloride were applied.…”
Section: In Vitro Propagationmentioning
confidence: 99%
“…These explants were later discarded. Sedlák and Paprstein (2007) used 0.15% mercuric chloride (HgCl2) solution for disinfection and observed that 50% of initial uncontaminated explants of cultivar Altaj died after the sterilization procedure. According to Debnath (2007) the most important and necessary step in vitro propagation of Vaccinium genus is regeneration from primary explants.…”
Section: In Vitro Propagationmentioning
confidence: 99%
See 2 more Smart Citations